OSEM luggage - Jasren, Crystal Marvella; Buing, Erzivericella; Johnny, Cindy; Rahmat, Nurazlina (Universiti Teknologi MARA, Kedah, 2023)
Traveling can be a very nerve-wracking experience for many travelers. Some contributing factors to traveling stress are losing their travel luggage, excess luggage weight, and carrying too many pieces of luggage. As reported in 2022, the cases of mishandled luggage at the airport increased by 100%. OSEM Luggage is a piece of smart luggage innovated to reduce some of these traveling stresses. OSEM Luggage is multi-function luggage supported with solar technology. This luggage has a unique application that can be downloaded into users’ smartphones. The primary function of this OSEM Luggage App is its ability to track the luggage’s whereabouts. Other functions, such as a place to buy traveling items, are also included to enhance users’ travel experience. In addition, OSEM Luggage also comes with an attached digital weighing scale so that users are aware of their luggage weight and avoid paying excess baggage fees or removing some of the items at the airport, which is deemed inconvenient. Another unique feature of OSEM luggage is that it has attached vacuum devices and bags to deflate traveling items to save luggage space, allowing users to bring more traveling items in small to medium size luggage.